Prediktívne faktory a liečba aseptickej pseudoartrózy diafýzy humeru - Popelka, V; Popelka, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2022)
PURPOSE OF THE STUDY Aseptic pseudoarthrosis (nonunion, PSA) of the humeral shaft is one of the serious complications in the treatment of fractures in this area. In a retrospective study, the authors described different methods of treating patients with this complication using predictive factors. MATERIAL AND METHODS Based on the definition of nonunion and the criteria, 14 patients (N=14) with the mean age of 56 years (32-78), namely 8 men and 6 women were included in the study. All patients were followed up clinically and radiologically at 1, 3, 6, 9, 12 months and every 3 months until the condition stabilized. The follow-up period was 11-72 months, with the average of 22 months. According to the AO classification, the fractures were classified as: 4-A1, 1-A2, 4-A3, 1-B1, 3-B2 and 1-C2. Based on the Weber-Čech classification, 2 cases of pseudoarthrosis were hypertrophic, 4 oligotrophic and 8 atrophic. According to the Non-Union Scoring System (NUSS), 5 patients reached the score under 25 points, 3 patients received 25-50 points, 4 patients 51-75 points and two patients over 76 points. In five cases, the fracture displacement index (FDI) was above 100%. In 11 patients, PSA was in the proximal and middle third and in three patients in the distal third of the humerus. METHODS Of the whole group (N=14), the nail was used in 5 cases (36%) - in 3 cases NUSS of up to 50 points and in 2 cases over 76 points. The plate was used in 9 cases (64%). In patients with NUSS of up to 50 points - in 1 case after conservative treatment, in 1 case for augmentation of nail, in 3 cases for augmentation of Prévot nails. In 4 cases with NUSS of 51-75 points a plate was replaced. Osteosynthesis was always supplemented by Judet's decortication or resection of atrophic bone and spongioplasty by autologous graft. RESULTS Shoulder function measured by the Constant Murley score (C-M) improved from 53 to 89 points (from the range of 36-76 points to the range of 75-100 points). The function of the elbow joint also improved, namely from the Mayo Elbow Performance Score (MEPS) of 65 points to 90 points (from the range of 45-70 points to the range of 80-100 points). In 11 cases (79%) the nonunion was healed and in 3 cases (21%) the failure to heal was reported. In the group with unhealed nonunions, in one case with NUSS of 51-75 points a thermoplastic casting was used and in two patients with NUSS above 76 points a palliative surgery was performed using a 12mm interlocking intramedullary nail. DISCUSSION The results of our study focused on the treatment of aseptic nonunion of the humeral shaft confirm the conclusions arrived at by other authors. As to the osteosynthesis materials, the plate remains the gold standard and provides sufficient stability for bone healing. For unhealed treatment-resistant PSA, we offer a stable intramedullary nail instead of prosthetic replacement or amputation, which provides good stability required for limb function. CONCLUSIONS When planning the treatment of aseptic pseudoarthrosis of the humeral shaft, it is necessary to have a thorough knowledge of etiopathogenesis with all predictive factors. The NUSS classification provides good guidance in treating this complication. Key words: aseptic nonunion, NUSS classification, predictive factors.
Keywords: Fracture Fixation, Internal; Humerus; Humans; lidé středního věku; Fracture Healing; Female; intramedulární fixace fraktury; Humeral Fractures; Prostate-Specific Antigen; výsledek terapie; lidé; fraktury humeru; hojení fraktur; humerus; vnitřní fixace fraktury; ženské pohlaví; Pseudarthrosis; Bone Plates; kostní destičky; Male; Middle Aged; Retrospective Studies; prostatický specifický antigen; Treatment Outcome; retrospektivní studie; mužské pohlaví; pseudoartróza; Fracture Fixation, Intramedullary